Symbiont coordinates stem cell proliferation, apoptosis, and morphogenesis of gut symbiotic organ in the stinkbug-Caballeronia symbiosis - Jang, Seonghan; Matsuura, Yu; Ishigami, Kota; Mergaert, Peter; Kikuchi, Yoshitomo (Frontiers in Physiology, 2023)
The bean bug Riptoruts pedestris obtains a specific bacterial symbiont, Caballeronia insecticola (Burkholderia insecticola), from the environmental soil and harbors it in the posterior midgut region that is composed of hundreds of crypts. While newly hatched aposymbiotic insects possess primordial midgut crypts with little or no lumen, colonization of C. insecticola triggers swift development of the symbiotic organ, forming enlarged and opened crypts, and the symbiont subsequently fills the luminal cavities of those mature crypts. The cellular processes of crypt development triggered by C. insecticola colonization are poorly understood. Here we identified a fundamental mechanism of the symbiont-mediated midgut development by investigating cell cycles of intestinal epithelial cells. Intestinal stem cells of the bean bug are located and proliferate at the crypt base. Differentiated enterocytes migrate upward along the epithelial cell layer of the crypt as the midgut develops, induction of apoptosis in enterocytes primarily occurred on the tip side of the crypts, and apoptotic cells then eventually were shed from the crypts into the hemolymph. The proliferation rate of the stem cells at the base of the crypts was low while a high apoptotic rate was observed at the crypt tip in aposymbiotic insects, resulting in undeveloped short crypts. On the contrary, the gut-colonizing C. insecticola promoted the proliferation of the stem cells at the base of crypts and simultaneously inhibited apoptosis at the tip of crypts, resulting in a net growth of the crypts and the generation of a crypt lumen that becomes colonized by the bacterial symbiont. These results demonstrated that the Caballeronia symbiont colonization induces the development of the midgut crypts via finely regulating the enterocyte cell cycles, enabling it to stably and abundantly colonize the generated spacious crypts of the bean bug host.